Thermal Expansion and Contraction of Geomembrane Liners Subjected to Solar Exposure and Backfilling - Take, W. A; Watson, E; Brachman, R. W. I; Rowe, R. K (Journal of geotechnical and geoenvironmental engineering, 2012)
AbstractGeomembranes (GMBs) are widely used as advective barriers in landfill liner systems. When exposed to the sun, GMBs exhibit a network of wrinkles as a result of thermal expansion. These wrinkles disrupt the intimate contact between the GMB and the underlying layer. If a hole is coincident with a GMB wrinkle then the space under the wrinkle has the potential to act as a preferential pathway for flow of contaminants. Thus, the size and shape of GMB wrinkles have implications for leakage rates through the composite liner system. However, wrinkles are only a concern if they persist after placement of backfill, which is currently a subject of debate. In this paper, wrinkles are induced in a 1.5-mm-thick, black high-density polyethylene strip GMB specimen overlying a geosynthetic clay liner using natural solar and laboratory energy sources. Particle image velocimetry techniques are employed to record cross-sectional wrinkle geometry during growth and subsequent backfilling. This cross-sectional geometry is found to follow a Gaussian shape in which the height increases with the temperature and the width remains relatively constant. The resulting relationships between the height and temperature permit an estimation of wrinkle height for a known coefficient of thermal expansion for the GMB and an estimate of wrinkle spacing. For the GMB material and conditions tested, the results of the backfilling experiments indicate that when covered with 230 mm of cool sand (21°C), wrinkles of initial height less than about 20 mm disappear completely, while larger wrinkles remain with a reduced height. Furthermore, wrinkles of 20 mm in height are observed to form with increases in GMB temperature of less than 5°C. With application to the field, these findings indicate that a GMB must be covered at or below its installation temperature to achieve a wrinkle-free installation.